Examining the impact of risk management practices on sustainable project performance in the construction industry: the role of stakeholder engagement - Song, Jianmin; Munyinda, Matakala; Adu Sarfo, Philip (Frontiers in Built Environment, 2025)
This study investigates the impact of risk management practices on sustainable project performance, specifically focusing on the mediating role of stakeholder engagement in the construction industry within emerging economies. It examines how risk identification, assessment, and mitigation contribute to sustainability’s environmental, economic, and social dimensions. Utilizing data collected from construction project managers involved in sustainability-driven projects, the findings confirm that all three risk management practices significantly enhance sustainable project performance. Furthermore, stakeholder engagement through communication, collaboration, and decision-making involvement plays a crucial mediating role, strengthening the effectiveness of risk management strategies in achieving sustainability goals.